Implementation of Analytical Hierarchy Process (AHP) for Determining Priority of Software Assessment in West Java Provincial Government Based on ISO/IEC 25010 (Case Study: Sapawarga Application) - Nisrina Nurhuda; Eko Darwiyanto; Sri Widowati (School of Computing, Telkom University, 2021)
The quality of the software is defined ISO as the totality of the features and characteristics of the product or services that depend on the ability to satisfy user needs. Sapawarga is software used to meet the needs of citizens in channeling aspirations, proposals, and obtaining information in one application. There are some negative comments about the app on Google’s app store. This indicates there are quality issues in sapawarga software. The results of a follow-up survey showed users of the application experienced a 45.20% decrease, due to the server not responding, difficulty finding information, etc. This research was conducted to evaluate the quality of the software based on ISO 25010 consisting of eight characteristics including functional suitability, reliability, usability, performance efficiency, maintainability, portability, security, and compatibility. The AHP pairing comparison method is used to select the three most important ISO characteristics. These three most important characteristics are then used to assess the application of sapawarga and propose recommendations for improvement. Based on expert judgment using AHP pair comparison method, the three characteristics that most affect the application of sapawarga are functional suitability, usability, and performance efficiency with interest rates of 24.9%, 23.2%, 16.5%.